Prognostic Value of Baseline Neutrophil-to-Lymphocyte Ratio in Outcome of Immune Checkpoint Inhibitors. (3rd July 2019) - Xie, Xianhe; Liu, Junjin; Yang, Haitao; Chen, Huijuan; Zhou, Sijing; Lin, Heng; Liao, Ziyuan; Ding, Yin; Ling, Liting; Wang, Xuewen
Abstract: A meta-analysis of 14 studies (16 cohorts) incorporating 1751 participants was performed to evaluate the correlation between baseline neutrophil-to-lymphocyte ratio (NLR) and outcome of immune checkpoint inhibitors (ICI). The pooled hazard ratio (HR) suggested elevated pretreatment NLR was associated with poor OS ( HR: 2.61, 95% confidence intervals (CI): 1.77–3.86, p  < 0.00001) and PFS ( HR: 1.74, 95% CI : 1.34–2.27, p  < 0.0001). Stratified analyses on tumor types, ICI agents, the cutoff value of NLR and study regions exhibited the similar outcomes. This study demonstrated that elevated NLR was a predictor of poor OS and PFS for ICI.